Penyuluhan Literasi Stunting tingkat Mahasiswa - Anggeraini, Yentri; Devana, Trisilia; Contessa, Emilia; Yusnilita, Nopa; Lastri, Neti; Afifah, Nurul (Jurnal Pengabdian Masyarakat (ABDIRA), 2025)
Currently, not only the health sector supports the government’s initiatives to prevent stunting, but universities are equally supportive. Therefore, this paper aims to engage students and disseminate knowledge about stunting or stunting in higher education to support government initiatives to prevent stunting in all sectors. This community service was provided through socializing, discussion, and question-answering sessions with students. The event, which was attended by 35 representatives from five faculties of Universitas Baturaja, began with socialization on stunting. It is a chronic malnutrition condition that stunts the growth and development of children. The socialization material included education on the effects of stunting, the importance of nutritional control, how to prevent stunting through a healthy, nutritious diet, and the role of students in preventing stunting. It can be concluded that students representing various faculties at Baturaja University gained knowledge about stunting literacy, in the other word, this program, has brought benefits to themselves and their surroundings in the context of preventing stunting.